Application of micellar enhanced ultrafiltration for the removal of soluble organic compounds present in produced water - Regis, Renata Jaeger (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2020.